Design And Fabrication Of Shape Memory Device - Mohammad Musa, Mohammad Taufiq Haiqal (Universiti Sains Malaysia, 2018)
Shape Memory Alloys (SMAs) have been considered as one of the most promising smart and advance materials. A lot of idea generated on using this advance material for implementation into various applications such as actuator, biomedical application and etc. Shape Memory Alloys demonstrate a unique ability to recover their original shape after deformation through a reversible thermo-elastic phase transformation, it allows shape memory alloys to recover large strains which can reach 8% the most. Among the commercially available shape memory alloys, nickel–titanium ones are outstanding due to their excellent performance and reliability. A case study approached was employed to demonstrate the workable two-way shape memory alloy. This study is aiming on the design and development of tool by utilizing the two-way shape memory effect. The idea is to combine both shape memory and pseudoelastic training. This method is to gain changes in the original hot shape together with the transformation temperatures after the training process, and the effective outcome of the cold shape. The shape set is an arc of 90o with 10cm length to for each of the sample to illustrate the movement of flower petal. The experiment of dealing the Nitinol wire with and without the presence of R-phase as it is the best realise that by supressing the R-phase able to increase the range of martensite values. Furthermore, the training method used for Nitinol wire to exhibit the two-way shape memory effect that gives respond towards the change of surrounding temperature. Thus, the NiTi shape memory alloy able to develop the two-way shape memory effect to perform the shape set for both martensite and austenite phase.